Theoretical Dialectics: A Commentary on Sampling Methodology and its Application - Turner, Jane (Archivaria, 1994)
The commentary argues that the methodological practice used in the two case studies (by Ellen Scheinberg and Evelyn Kolish) demonstrates that a theoretical consensus regarding appraisal has been reached, and is derived from the two central principles of appraisal: impartiality and provenance. A major factor that has contributed to the new awareness of the value of theory comes from the fact that the study of electronic records has forced us to refocus our thinking from the study of particular records in a particular form, to a study of activities from which our society requires documentation. RÉSUMÉ Ce commentaire soutient que la méthodologie utilisée dans les deux cas d'espèce par Ellen Scheinberg et Evelyn Kolish démontre qu'un consensus théorique sur l'évaluation a été atteint et que celui-ci est fondé sur les deux principes fondamentaux de l'évaluation à savoir: l'impartialité et la provenance. L'une des principales raisons qui explique cette prise de conscience de l'intérêt de la théorie vient du fait que l'étude des dossiers électroniques a forcé les archivistes à réorienter leur pensée de l'étude des dossiers particuliers sur un support précis à une étude d'activités pour lesquels notre société requiert de l'information.